METHOD TO EVALUATE THE POSSIBILITY OF ESTABLISHING DISSERTATION COUNCIL IN THE ORGANIZATION, ADMINISTERED BY THE MINISTRY OF EDUCATION AND SCIENCE OF RUSSIAN FEDERATION - Sergey I. Pakhomov; German I. Dmitriev; Valery A. Gurtov; Lyudmila V. Shchegoleva (Высшее образование в России)
The paper presents a methodology for evaluating the possibility of creating/ functioning of dissertation council in the organizations, administered by the Ministry of Education and Science of Russian Federation. According to the provisions governing the procedure for the creation of the dissertation council, the founder of the organization has to consent the opening of the dissertation council on the base of the organization. To do so, the founder must assess the level of qualification of the dissertation council. We propose method of this assessment. The method is based on indicators of scientific and human potential of the organization as a whole, and by the area of science and by scientific specialties, in comparison with the values of the indicators for all subordinate organizations. The technique offers a ranking of organizations and dividing them into three groups, which determine the possibility of establishing an independent and united dissertation council on the basis of the organization.